2008
DOI: 10.1007/s00216-008-2315-2
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of xenobiotic-metabolizing cytochromes P450

Abstract: The regulation of cytochromes P450 (CYPs) by induction mediated by xenobiotics is well known. Our team has discovered an additional important regulation of xenobiotic-metabolizing CYPs by phosphorylation. Individual CYPs are phosphorylated by different protein kinases, leading to CYP isoenzyme-selective changes in the metabolism of individual substrates and consequent profound changes in the control of mutagenic and cytotoxic metabolites. Some CYPs are phosphorylated by protein kinase C and some by the cyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, individual species of CYPs are known to be phosphorylated by PKA, in response to elevated levels of cyclic adenosine monophosphate (cAMP), triggered by xenobiotics. In addition, cAMP levels influence the nuclear translocation of AHR, connecting these two pathways and their impact on CYP activity [40]. …”
Section: Discussionmentioning
confidence: 99%
“…However, individual species of CYPs are known to be phosphorylated by PKA, in response to elevated levels of cyclic adenosine monophosphate (cAMP), triggered by xenobiotics. In addition, cAMP levels influence the nuclear translocation of AHR, connecting these two pathways and their impact on CYP activity [40]. …”
Section: Discussionmentioning
confidence: 99%
“…This suggests CMS-induced modification of agomelatine effect at a posttranscriptional or posttranslational level. It was found that an increase in enzyme protein phosphorylation might diminish the CYP2B activity [ 65 ] or might predispose the enzyme to degradation [ 66 ]. It is conceivable that stress-induced elevation in the concentrations of peripheral catecholamines might affect hepatocyte signaling pathways and the CYP2B protein phosphorylation and, in turn, enzyme protein level and activity in agomelatine-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…The observed inconsistencies between the levels of mRNA, protein and enzyme activities suggest some posttranscriptional modifications. This may happen, e.g., when reactive drug metabolites are formed (which may interact with RNA or enzyme protein) or when cell signaling is altered (e.g., cAMP production), thereby affecting the phosphorylation processes and, in turn, activation of transcription factors or enzyme protein synthesis, function or degradation [ 39 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…After obtaining the general information on a group (or a family) of biomolecules that are similar in both physicochemical and biological properties, the individual information (e.g., quantity and bioactivity) of a targeted member is often desired in understanding its unique role during a certain life process and the diagnosis of a disease and subsequent drug development. , As a typical example of such a family of biomolecules, cytochrome P450 (a superfamily of heme-thiolated low-expressed monooxygenase) contains more than 50 homologous enzymes of functional significance, which are responsible for the metabolism of a variety of xenobiotics and play key roles in their activation and then oxidation of the inactive C–H bonds in drugs and exogenous compounds . The regulation of their quantities and activities are closely connected to a well-balanced homeostasis and/or an abnormal physiological process of metabolic disturbance, diseases, and even carcinoma. As one of the most important members among this family, cytochrome P450 3A4 (CYP3A4) occupies the central position during drugs and xenobiotics oxidative metabolism, accounting for approximately 50% of the total expressed P450 content in the human liver and participating in greater than half the hepatic toxicological processes. , Therefore, its quantification and activity measurement are important for the diagnosis of liver abnormality and have a great significance for metabolomic study and target-directed drug design. Its assay can be performed using traditional protocols such as the Bradford method and enzyme-linked immunosorbent assay (ELISA) through isotope-coded affinity tag (ICAT) and isobaric tags for relative and absolute quantitation (iTRAQ) based electrospray ionization/matrix-assisted laser desorption ionization- mass spectrometry (ESI/MALDI-MS). ELISA using monoantibodies is usually used in P450 detection dependent mainly on the certain structural interactions between an antigen and its antibody while cross-reactivities of antibodies recognization occur frequently; , the ESI/MALDI-MS techniques and corresponding methods greatly depend on precise protein digestion and the synthesis of isotopic signature peptide standards .…”
mentioning
confidence: 99%